Stable flame-retardant gel polymer for electrolyte
By using the combination of hyperbranched polyethylene oxide with lithium salt and solvent in the lithium battery electrolyte, a highly branched three-dimensional network structure is formed, and through the phosphorus-sulfur collaborative flame retardant system, the problem that existing electrolyte materials cannot take into account both the conductivity and flame retardant properties are solved, and high ionic conductivity and good flame retardant properties are achieved.
Patent Information
- Application Number
- CN202510368451.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-27
AI Technical Summary
The existing lithium battery electrolyte materials cannot take into account both the conductivity and flame retardancy.
A stable flame retardant gel polymer for electrolyte is used to form a highly branched three-dimensional network structure through the combination of hyperbranched polyethylene oxide (PEO) with lithium salts and solvents, and the flame retardant performance of the material is improved through a phosphorus-sulfur collaborative flame retardant system.
It achieves high ionic conductivity and good flame retardant performance, meets the fast charging needs of high-energy-density batteries, and improves the thermal runaway safety of lithium batteries.
Smart Images

Figure CN119875129A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer electrolytes for lithium batteries, and in particular to a stable flame-retardant gel polymer for electrolyte and a preparation method thereof. Background Art
[0002] Lithium batteries are widely used in electric vehicles, energy storage and other fields due to their high energy density and long cycle life, but their safety issues (such as combustion and explosion caused by thermal runaway) limit their further development. Although traditional liquid electrolytes have high ionic conductivity, they are flammable and easy to leak, and they need to add flame retardants to improve safety. However, added flame retardants are easy to agglomerate and migrate, resulting in a decrease in electrolyte performance; although traditional solid electrolytes have high safety, inhibit dendrite growth and good thermal stability, they have low ionic conductivity at room temperature, high interfacial impedance and complex preparation process.
[0003] Polymer electrolytes (such as polyethylene oxide, PEO) have become a research hotspot due to their good film-forming properties and high safety, but their high crystallinity leads to low room temperature ionic conductivity and lack of intrinsic flame retardancy. Existing improvement methods include: 1. Copolymerization modification: Introducing flexible segments (such as polyethylene glycol) to reduce crystallinity, but the choice of copolymer monomers is limited, and it is difficult to achieve high conductivity and flame retardancy at the same time.
[0004] 2. Adding nanofillers: such as Al2O3, SiO2, etc., although they can inhibit crystallization, the fillers have poor dispersion and are prone to form ion transport barriers.
[0005] 3. Gel design: Linear PEO is mixed with solvent / plasticizer to form gel, which increases the conductivity to 10 -6 ~10 -4 S / cm, but solvent evaporation or migration leads to insufficient stability. Summary of the invention
[0006] In view of this, the purpose of the present invention is to provide a stable flame-retardant gel polymer for electrolyte and a preparation method thereof, so as to solve the problem that the existing electrolyte materials cannot take both conductivity and flame retardancy into account.
[0007] Based on the above purpose, the present invention provides a stable flame-retardant gel polymer for electrolyte, comprising the following raw materials in parts by weight: hyperbranched polyethylene oxide PEO: 20-30 parts, lithium salt: 15-20 parts and solvent: 60-70 parts; The specific preparation process of the hyperbranched PEO is as follows: (1) a. The preparation equation of the main chain A polymer is as follows: Formula (1) b. The preparation process of the main chain A polymer is as follows: tris(hydroxymethyl)phosphine oxide is dissolved in anhydrous toluene, a pressure of 3-5 MPa is applied to ethylene oxide to ensure that ethylene oxide is in liquid state, and liquid ethylene oxide and tris(hydroxymethyl)phosphine oxide solution are pumped into a mixer by a metering pump using a continuous flow microchannel reactor. After uniform mixing, the temperature in the reactor is maintained at 70-90°C, the pressure is 1-3 MPa, the flow rate is 3-5 ml / min, and the residence time is 5-10 min. Methanol containing 0.1% hydrochloric acid is added to the discharge port to quench the reaction, and the solvent is removed by reduced pressure distillation. The product is washed with ethanol and dried to obtain a main chain A polymer. The product is characterized by P NMR and infrared spectroscopy. A peak is observed in P NMR, indicating that the product contains P. In the infrared spectrum, a peak of 1000-1500 cm -1 There are two strong peaks at 900-950 cm - ¹ and 820-830 cm - ¹No peaks were observed, indicating that the product contained both P=O and COC functional groups, and all the epoxy groups had been ring-opened and disappeared, proving that the product was formed by ring-opening of ethylene oxide and polymerization with trimethylolphosphine oxide; (2) i. The preparation equation of branched B polymer is as follows: Formula (2) ii. The preparation process of the branched B polymer is as follows: 2,2'-[methylenebissulfonyl]diethanol is dissolved in anhydrous tetrahydrofuran, a pressure of 3-5 MPa is applied to ethylene oxide to ensure that ethylene oxide is in liquid state, and liquid ethylene oxide and 2,2'-[methylenebissulfonyl]diethanol solution are pumped into a mixer through a metering pump using a continuous flow microchannel reactor. After uniform mixing, the temperature in the reactor is maintained at 70-80°C, the pressure is 1-3 MPa, the flow rate is 3-5 ml / min, and the residence time is 5-10 min. Methanol containing 0.1% hydrochloric acid is added to the discharge port to quench the reaction, and the solvent is removed by reduced pressure distillation. The product is washed with ethanol and dried to obtain the branched B polymer. The product is characterized by H NMR and infrared spectroscopy. In NMR, a peak at 3.68-3.61 ppm was observed, which was the obvious methylene peak position on the polymer chain. This indicated that a large amount of ethylene oxide was ring-opened and polymerized with 2,2'-[methylenebissulfonyl] diethanol. In the infrared spectrum, a peak at 1000-1500 cm -1 There are three very strong peaks, corresponding to the S=O and CS=O vibrations of the ether bond, sulfonyl group of the PEO main chain, reflecting the structural characteristics of the branched polymer B prepared by ethylene oxide initiated by 2,2'-[methylenebissulfonyl]bisethanol; (3) Add methyltrimethoxysilane to an ethanol / water mixed solution, stir at room temperature for 30-60 minutes to obtain a silane solution, add the main chain A polymer and the branched chain B polymer to tetrahydrofuran, stir at room temperature for 30-60 minutes, add the silane solution, heat to 60-80°C, react for 4-8 hours, cool to room temperature, precipitate the product in ether, wash with ethanol, and dry to obtain hyperbranched PEO. The reaction process is shown in the following diagram: Formula (3) Preferably, in said (1), the weight ratio of trimethylolphosphine oxide, ethylene oxide and toluene is 1:15-25:10-20.
[0008] Preferably, in said (2), the weight ratio of 2,2'-[methylenebissulfonyl]diethanol, ethylene oxide and anhydrous tetrahydrofuran is 1:40-50:10-20.
[0009] Preferably, in said (3), the weight ratio of methyltrimethoxysilane, main chain A polymer, side chain B polymer, tetrahydrofuran and ethanol / water mixed solution is 1:2-4:6-12:100-120:10-20.
[0010] Preferably, the ethanol / water mixed solution in (3) refers to a mixture of ethanol and water in a weight ratio of 95:5.
[0011] Preferably, the lithium salt is one or more of lithium perchlorate, lithium trifluoromethanesulfonate, lithium hexafluorophosphate or lithium tetrafluoroborate.
[0012] Preferably, the solvent is a mixture of triethyl phosphate and ethylene carbonate in a weight ratio of 1:0.05.
[0013] Furthermore, the present invention also provides a method for preparing the above-mentioned stable flame-retardant gel polymer for electrolyte, which specifically comprises the following steps: S1. Adding a lithium salt to a solvent and stirring to form a liquid electrolyte; S2. Hyperbranched PEO is added to a liquid electrolyte to obtain a stable flame-retardant gel polymer for electrolyte.
[0014] Beneficial effects of the present invention: 1. The hyperbranched PEO prepared by the present invention forms a highly branched three-dimensional network structure through the rational combination of rigid phosphorus groups in the main chain and flexible sulfone groups in the side chains. This structure effectively inhibits the crystallization behavior of PEO, increases the proportion of amorphous regions, and thus improves segment mobility and the density of lithium ion migration channels. At the same time, the strong polarity of the sulfone group forms a coordination effect with lithium salts (such as lithium trifluoromethanesulfonate), promotes the dissociation of lithium salts, improves the ionic conductivity of the material, and meets the fast charging requirements of high energy density batteries.
[0015] 2. The present invention introduces phosphorus-containing groups (P=O) into the PEO main chain through molecular structure design, and introduces sulfone-containing groups (O=S=O) into the side chains to form a phosphorus-sulfur synergistic flame retardant system. When phosphorus is burned, it generates phosphoric anhydride, which promotes the formation of a carbon layer, while the sulfone group decomposes to produce SO2 gas to dilute oxygen. The synergistic effect of the two makes the material's flame retardant performance far superior to that of general linear PEO materials. This intrinsic flame retardant property does not require the addition of external flame retardants, avoids the problems of uneven dispersion of traditional additive flame retardants and poor compatibility with electrolytes, while maintaining the homogeneity and stability of the material, significantly improving the thermal runaway safety of lithium batteries.
[0016] 3. The present invention adopts continuous flow microchannel reactor technology to synthesize hyperbranched PEO, which has significant environmental protection and high efficiency advantages compared to traditional intermittent polymerization processes. The continuous flow process achieves efficient copolymerization by precisely controlling the reaction parameters, shortens the reaction residence time, and improves efficiency. At the same time, the high mass transfer and heat transfer characteristics of the microchannel reactor reduce the generation of by-products, reduce the discharge of three wastes, and reduce the amount of solvents such as toluene and tetrahydrofuran, which is in line with the concept of green chemistry. In addition, the continuous flow process can achieve large-scale production through modular design, with small differences between product batches, suitable for industrial amplification, and provides technical support for the low-cost and sustainable preparation of high-performance electrolytes. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Main chain A polymer 31 P NMR spectrum; Figure 2 is the H NMR spectrum of the branched B polymer; Figure 3 is the infrared spectrum of the main chain A polymer; Figure 4 This is the infrared spectrum of branched B polymer. DETAILED DESCRIPTION
[0018] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0019] The sources of the reagents and raw materials used in the embodiments of the present invention are as follows: Tris(hydroxymethyl)phosphine oxide was purchased from Ningbo Chemical Raw Materials Co., Ltd. with a purity of 99%; ethylene oxide was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with a purity of 99.5%; 2,2'-[methylenebissulfonyl]diethanol was purchased from Shaanxi Didu Pharmaceutical Chemical Co., Ltd. with a purity of 98%; methyltrimethoxysilane was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with a purity of 98%; triethyl phosphate was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with a purity of 98%; ethylene carbonate was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with a purity of 98%; lithium trifluoromethanesulfonate was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with a purity of 99.5%.
[0020] Example 1: A specific preparation method of a stable flame-retardant gel polymer for electrolyte, comprising the following process: (1) 20 g of tris(hydroxymethyl)phosphine oxide was dissolved in 200 g of anhydrous toluene to prepare a tris(hydroxymethyl)phosphine oxide solution. A pressure of 3 MPa was applied to ethylene oxide to ensure that ethylene oxide was in liquid state. 300 g of liquid ethylene oxide and tris(hydroxymethyl)phosphine oxide solution were pumped into a mixer by a metering pump using a continuous flow microchannel reactor. After uniform mixing, the temperature was maintained at 70° C., the pressure was 1 MPa, the flow rate was 3 ml / min, and the residence time was 5 min in the reactor. Methanol containing 0.1% hydrochloric acid was added to the discharge port to quench the reaction. The solvent was removed by distillation under reduced pressure. The product was washed with ethanol and dried to obtain a main chain A polymer. (2) 10 g of 2,2'-[methylenebissulfonyl]diethanol was dissolved in 100 g of anhydrous tetrahydrofuran to prepare a 2,2'-[methylenebissulfonyl]diethanol solution. A pressure of 3 MPa was applied to ethylene oxide to ensure that ethylene oxide was in a liquid state. 400 g of liquid ethylene oxide and 2,2'-[methylenebissulfonyl]diethanol solution were pumped into a mixer through a metering pump using a continuous flow microchannel reactor. After uniform mixing, the temperature in the reactor was maintained at 70° C., the pressure was 1 MPa, the flow rate was 3 ml / min, and the residence time was 5 min. Methanol containing 0.1% hydrochloric acid was added to the discharge port to quench the reaction. The solvent was removed by distillation under reduced pressure. The product was washed with ethanol and dried to obtain a branched B polymer. (3) Add 30 g of methyltrimethoxysilane to 300 g of ethanol / water mixed solution (ethanol and water are mixed in a weight ratio of 95:5), stir at room temperature for 30 min to obtain a silane solution, add 60 g of main chain A polymer and 180 g of branched chain B polymer to 3 kg of tetrahydrofuran, stir at room temperature for 30 min, add the silane solution, heat to 60 ° C, react for 4 h, cool to room temperature, precipitate the product in ether, wash with ethanol, and dry to obtain hyperbranched PEO; (4) adding 150 g of lithium trifluoromethanesulfonate to 600 g of a solvent prepared by mixing triethyl phosphate and ethylene carbonate in a weight ratio of 1:0.05, and stirring to form a liquid electrolyte; (5) 200 g of hyperbranched PEO was added to the liquid electrolyte to obtain a stable flame-retardant gel polymer for electrolyte.
[0021] Example 2: A specific preparation method of a stable flame-retardant gel polymer for electrolyte, comprising the following process: (1) 20 g of tris(hydroxymethyl)phosphine oxide was dissolved in 150 g of anhydrous toluene to prepare a tris(hydroxymethyl)phosphine oxide solution. A pressure of 4 MPa was applied to ethylene oxide to ensure that the ethylene oxide was in a liquid state. 400 g of liquid ethylene oxide and the tris(hydroxymethyl)phosphine oxide solution were pumped into a mixer by a metering pump using a continuous flow microchannel reactor. After uniform mixing, the temperature was maintained at 80° C., the pressure was 2 MPa, the flow rate was 4 ml / min, and the residence time was 8 min in the reactor. Methanol containing 0.1% hydrochloric acid was added to the discharge port to quench the reaction. The solvent was removed by distillation under reduced pressure. The product was washed with ethanol and dried to obtain a main chain A polymer. (2) 10 g of 2,2'-[methylenebissulfonyl]diethanol was dissolved in 150 g of anhydrous tetrahydrofuran to prepare a 2,2'-[methylenebissulfonyl]diethanol solution. A pressure of 4 MPa was applied to ethylene oxide to ensure that ethylene oxide was in a liquid state. 450 g of liquid ethylene oxide and 2,2'-[methylenebissulfonyl]diethanol solution were pumped into a mixer through a metering pump using a continuous flow microchannel reactor. After uniform mixing, the temperature in the reactor was maintained at 75° C., the pressure was 2 MPa, the flow rate was 4 ml / min, and the residence time was 8 min. Methanol containing 0.1% hydrochloric acid was added to the discharge port to quench the reaction. The solvent was removed by distillation under reduced pressure. The product was washed with ethanol and dried to obtain a branched B polymer. (3) Add 30 g of methyltrimethoxysilane to 450 g of ethanol / water mixed solution (ethanol and water are mixed in a weight ratio of 95:5), stir at room temperature for 45 min to obtain a silane solution, add 90 g of main chain A polymer and 270 g of branched chain B polymer to 3.3 kg of tetrahydrofuran, stir at room temperature for 45 min, add the silane solution, heat to 70 ° C, react for 6 h, cool to room temperature, precipitate the product in ether, wash with ethanol, and dry to obtain hyperbranched PEO; (4) adding 175 g of lithium trifluoromethanesulfonate to 650 g of a solvent prepared by mixing triethyl phosphate and ethylene carbonate in a weight ratio of 1:0.05, and stirring to form a liquid electrolyte; (5) 250 g of hyperbranched PEO was added to the liquid electrolyte to obtain a stable flame-retardant gel polymer for electrolyte.
[0022] Example 3: A specific preparation method of a stable flame-retardant gel polymer for electrolyte, comprising the following process: (1) 20 g of tris(hydroxymethyl)phosphine oxide was dissolved in 700 g of anhydrous toluene to prepare a tris(hydroxymethyl)phosphine oxide solution. A pressure of 5 MPa was applied to ethylene oxide to ensure that the ethylene oxide was in a liquid state. 500 g of liquid ethylene oxide and the tris(hydroxymethyl)phosphine oxide solution were pumped into a mixer by a metering pump using a continuous flow microchannel reactor. After uniform mixing, the temperature was maintained at 90° C., the pressure was 3 MPa, the flow rate was 5 ml / min, and the residence time was 10 min in the reactor. Methanol containing 0.1% hydrochloric acid was added to the discharge port to quench the reaction. The solvent was removed by distillation under reduced pressure. The product was washed with ethanol and dried to obtain a main chain A polymer. (2) 10 g of 2,2'-[methylenebissulfonyl]diethanol was dissolved in 200 g of anhydrous tetrahydrofuran to prepare a 2,2'-[methylenebissulfonyl]diethanol solution. A pressure of 5 MPa was applied to ethylene oxide to ensure that ethylene oxide was in a liquid state. 500 g of liquid ethylene oxide and 2,2'-[methylenebissulfonyl]diethanol solution were pumped into a mixer through a metering pump using a continuous flow microchannel reactor. After uniform mixing, the temperature in the reactor was maintained at 80° C., the pressure was 3 MPa, the flow rate was 5 ml / min, and the residence time was 10 min. Methanol containing 0.1% hydrochloric acid was added to the discharge port to quench the reaction. The solvent was removed by distillation under reduced pressure. The product was washed with ethanol and dried to obtain a branched B polymer. (3) Add 40 g of methyltrimethoxysilane to 800 g of ethanol / water mixed solution (ethanol and water are mixed in a weight ratio of 95:5), stir at room temperature for 60 min to obtain a silane solution, add 160 g of main chain A polymer and 480 g of branched chain B polymer to 4.8 kg of tetrahydrofuran, stir at room temperature for 60 min, add the silane solution, heat to 80 ° C, react for 8 h, cool to room temperature, precipitate the product in ether, wash with ethanol, and dry to obtain hyperbranched PEO; (4) adding 200 g of lithium trifluoromethanesulfonate to 700 g of a solvent prepared by mixing triethyl phosphate and ethylene carbonate in a weight ratio of 1:0.05, and stirring to form a liquid electrolyte; (5) 300 g of hyperbranched PEO was added to the liquid electrolyte to obtain a stable flame-retardant gel polymer for electrolyte.
[0023] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that the main chain A polymer is directly added to the liquid electrolyte, and the specific process is as follows: A specific preparation method of a stable flame-retardant gel polymer for electrolyte comprises the following steps: (1) 20 g of tris(hydroxymethyl)phosphine oxide was dissolved in 150 g of anhydrous toluene to prepare a tris(hydroxymethyl)phosphine oxide solution. A pressure of 4 MPa was applied to ethylene oxide to ensure that the ethylene oxide was in a liquid state. 400 g of liquid ethylene oxide and the tris(hydroxymethyl)phosphine oxide solution were pumped into a mixer by a metering pump using a continuous flow microchannel reactor. After uniform mixing, the temperature was maintained at 80° C., the pressure was 2 MPa, the flow rate was 4 ml / min, and the residence time was 8 min in the reactor. Methanol containing 0.1% hydrochloric acid was added to the discharge port to quench the reaction. The solvent was removed by distillation under reduced pressure. The product was washed with ethanol and dried to obtain a main chain A polymer. (2) adding 175 g of lithium trifluoromethanesulfonate to 650 g of a solvent prepared by mixing triethyl phosphate and ethylene carbonate in a weight ratio of 1:0.05, and stirring to form a liquid electrolyte; (3) 250 g of the main chain A polymer was added into the liquid electrolyte to obtain a stable flame-retardant gel polymer for electrolyte.
[0024] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that the branched B polymer is directly added to the liquid electrolyte. The specific process is as follows: A specific method for preparing a stable flame-retardant gel polymer for electrolyte comprises the following steps: (1) 10 g of 2,2'-[methylenebissulfonyl]diethanol was dissolved in 150 g of anhydrous tetrahydrofuran to prepare a 2,2'-[methylenebissulfonyl]diethanol solution. A pressure of 4 MPa was applied to ethylene oxide to ensure that ethylene oxide was in a liquid state. 450 g of liquid ethylene oxide and 2,2'-[methylenebissulfonyl]diethanol solution were pumped into a mixer by a metering pump using a continuous flow microchannel reactor. After uniform mixing, the temperature in the reactor was maintained at 75° C., the pressure was 2 MPa, the flow rate was 4 ml / min, and the residence time was 8 min. Methanol containing 0.1% hydrochloric acid was added to the discharge port to quench the reaction. The solvent was removed by distillation under reduced pressure. The product was washed with ethanol and dried to obtain a branched B polymer. (2) adding 175 g of lithium trifluoromethanesulfonate to 650 g of a solvent prepared by mixing triethyl phosphate and ethylene carbonate in a weight ratio of 1:0.05, and stirring to form a liquid electrolyte; (3) 250 g of the branched B polymer was added to the liquid electrolyte to obtain a stable flame-retardant gel polymer for electrolyte.
[0025] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that polyethylene oxide is added to the liquid electrolyte, and the specific process is as follows: A specific preparation method of a stable flame-retardant gel polymer for electrolyte comprises the following steps: (1) adding 175 g of lithium trifluoromethanesulfonate to 650 g of a solvent prepared by mixing triethyl phosphate and ethylene carbonate in a weight ratio of 1:0.05, and stirring to form a liquid electrolyte; (2) 250 g of polyethylene oxide was added to the liquid electrolyte to obtain a stable flame-retardant gel polymer for electrolyte.
[0026] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that: when synthesizing hyperbranched PEO, the weight ratio of the main chain A polymer and the branched chain B polymer is 1:1, and the specific process is as follows: A specific preparation method of a stable flame-retardant gel polymer for electrolyte comprises the following steps: (1) 20 g of tris(hydroxymethyl)phosphine oxide was dissolved in 150 g of anhydrous toluene to prepare a tris(hydroxymethyl)phosphine oxide solution. A pressure of 4 MPa was applied to ethylene oxide to ensure that the ethylene oxide was in a liquid state. 400 g of liquid ethylene oxide and the tris(hydroxymethyl)phosphine oxide solution were pumped into a mixer by a metering pump using a continuous flow microchannel reactor. After uniform mixing, the temperature was maintained at 80° C., the pressure was 2 MPa, the flow rate was 4 ml / min, and the residence time was 8 min in the reactor. Methanol containing 0.1% hydrochloric acid was added to the discharge port to quench the reaction. The solvent was removed by distillation under reduced pressure. The product was washed with ethanol and dried to obtain a main chain A polymer. (2) 10 g of 2,2'-[methylenebissulfonyl]diethanol was dissolved in 150 g of anhydrous tetrahydrofuran to prepare a 2,2'-[methylenebissulfonyl]diethanol solution. A pressure of 4 MPa was applied to ethylene oxide to ensure that ethylene oxide was in a liquid state. 450 g of liquid ethylene oxide and 2,2'-[methylenebissulfonyl]diethanol solution were pumped into a mixer through a metering pump using a continuous flow microchannel reactor. After uniform mixing, the temperature in the reactor was maintained at 75° C., the pressure was 2 MPa, the flow rate was 4 ml / min, and the residence time was 8 min. Methanol containing 0.1% hydrochloric acid was added to the discharge port to quench the reaction. The solvent was removed by distillation under reduced pressure. The product was washed with ethanol and dried to obtain a branched B polymer. (3) Add 90g of methyltrimethoxysilane to 1.35kg of ethanol / water mixed solution (ethanol and water are mixed in a weight ratio of 95:5), stir at room temperature for 45min to obtain a silane solution, add 270g of main chain A polymer and 270g of branched chain B polymer to 9.9kg of tetrahydrofuran, stir at room temperature for 45min, add the silane solution, heat to 70°C, react for 6h, cool to room temperature, precipitate the product in ether, wash with ethanol, and dry to obtain branched PEO; (4) adding 175 g of lithium trifluoromethanesulfonate to 650 g of a solvent prepared by mixing triethyl phosphate and ethylene carbonate in a weight ratio of 1:0.05, and stirring to form a liquid electrolyte; (5) 250 g of hyperbranched PEO was added to the liquid electrolyte to obtain a stable flame-retardant gel polymer for electrolyte.
[0027] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that when synthesizing hyperbranched PEO, the weight ratio of the main chain A polymer to the branched chain B polymer is 1:6, and the specific process is as follows: A specific preparation method of a stable flame-retardant gel polymer for electrolyte comprises the following steps: (1) 20 g of tris(hydroxymethyl)phosphine oxide was dissolved in 150 g of anhydrous toluene to prepare a tris(hydroxymethyl)phosphine oxide solution. A pressure of 4 MPa was applied to ethylene oxide to ensure that the ethylene oxide was in a liquid state. 400 g of liquid ethylene oxide and the tris(hydroxymethyl)phosphine oxide solution were pumped into a mixer by a metering pump using a continuous flow microchannel reactor. After uniform mixing, the temperature was maintained at 80° C., the pressure was 2 MPa, the flow rate was 4 ml / min, and the residence time was 8 min in the reactor. Methanol containing 0.1% hydrochloric acid was added to the discharge port to quench the reaction. The solvent was removed by distillation under reduced pressure. The product was washed with ethanol and dried to obtain a main chain A polymer. (2) 20 g of 2,2'-[methylenebissulfonyl]diethanol was dissolved in 300 g of anhydrous tetrahydrofuran to prepare a 2,2'-[methylenebissulfonyl]diethanol solution. A pressure of 4 MPa was applied to ethylene oxide to ensure that ethylene oxide was in a liquid state. 900 g of liquid ethylene oxide and 2,2'-[methylenebissulfonyl]diethanol solution were pumped into a mixer through a metering pump using a continuous flow microchannel reactor. After uniform mixing, the temperature in the reactor was maintained at 75° C., the pressure was 2 MPa, the flow rate was 4 ml / min, and the residence time was 8 min. Methanol containing 0.1% hydrochloric acid was added to the discharge port to quench the reaction. The solvent was removed by distillation under reduced pressure. The product was washed with ethanol and dried to obtain a branched B polymer. (3) Add 30 g of methyltrimethoxysilane to 450 g of ethanol / water mixed solution (ethanol and water are mixed in a weight ratio of 95:5), stir at room temperature for 45 min to obtain a silane solution, add 90 g of main chain A polymer and 540 g of branched chain B polymer to 3.3 kg of tetrahydrofuran, stir at room temperature for 45 min, add the silane solution, heat to 70 ° C, react for 6 h, cool to room temperature, precipitate the product in ether, wash with ethanol, and dry to obtain branched PEO; (4) adding 175 g of lithium trifluoromethanesulfonate to 650 g of a solvent prepared by mixing triethyl phosphate and ethylene carbonate in a weight ratio of 1:0.05, and stirring to form a liquid electrolyte; (5) 250 g of hyperbranched PEO was added to the liquid electrolyte to obtain a stable flame-retardant gel polymer for electrolyte.
[0028] Performance Test: Ionic conductivity test: The ionic conductivity of the samples prepared in Examples 1-3 and Comparative Examples 1-5 at 25°C, 50°C and 70°C was tested, and the experimental results are shown in Table 1. Flame retardant performance test: The hyperbranched PEO in Examples 1-3, the main chain A polymer in Comparative Example 1, the branched chain B polymer in Comparative Example 2, the polyethylene oxide in Comparative Example 3, and the branched PEO in Comparative Examples 4-5 were made into films with specifications of 120mm×10mm×3mm, and vertical combustion tests and limiting oxygen index tests were carried out. The experimental results are shown in Table 2.
[0029] Table 1 Ionic conductivity
[0030] Table 2 Flame retardant properties
[0031] Data Analysis: It can be seen from the experimental data in Table 1 and Table 2 that Examples 1-3 use a stable flame-retardant gel polymer for electrolyte prepared by the present invention, which has excellent ionic conductivity and good stable flame retardant properties, among which Example 2 has the best comprehensive performance, and has excellent ionic conductivity while maintaining good flame retardant properties. This may be because the main chain A polymer and the branched chain B polymer form a hyperbranched structure under the action of the silane coupling agent, which reduces the crystallinity of the material, improves the mobility of the chain segments, and promotes ion transport. The hyperbranched structure also provides a large number of terminal functional groups, enhances the coordination effect with the lithium salt, and improves the ion dissociation efficiency; the P=O group and the O=S=O group form a dense carbon layer during combustion, which inhibits the release of heat and combustible gases, so that the limiting oxygen index of Examples 1-3 is ≥31.3%, and all reach V0 level flame retardancy.
[0032] It can be seen from the data of Comparative Example 1 and Example 2 that the ionic conductivity of Comparative Example 1 is significantly reduced. This may be because the material prepared in Comparative Example 1 contains only the phosphorus-containing main chain A polymer and lacks the flexible chain segment of the branched chain B polymer, which makes the molecular chain easy to crystallize and inhibits the movement of the chain segment. At the same time, without the sulfur-containing group of the branched chain B polymer, the phosphorus-sulfur synergistic flame retardant effect is lost, the fire resistance level of the material is reduced, and the limiting oxygen index is also lower than that of Example 2.
[0033] It can be seen from the data of Comparative Example 2 and Example 2 that the ion conductivity of Comparative Example 2 is far inferior to that of Example 2, and the flame retardant performance has also decreased. This may be because the flexible structure of the branched B polymer reduces the crystallinity, but lacks the skeleton structure provided by the main chain A polymer, the degree of polymer branching is insufficient, and the ion transmission channel is disordered, which affects the ion conductivity of the material. At the same time, the material prepared in Comparative Example 2 only contains the sulfur-containing branched B polymer and lacks the phosphorus element of the main chain A. When the material burns, a phosphorus-containing carbon layer cannot be formed, resulting in a decrease in the flame retardant performance of the material.
[0034] From the data of Comparative Example 3 and Example 2, it can be seen that the various performances of Comparative Example 3 are very different from those of Example 2. This may be because the linear molecular chain of polyethylene oxide used in Comparative Example 3 is highly crystallized, which will form an ion transmission barrier, and lacks polar groups coordinated with lithium salts (such as P=O, O=S=O), the ion dissociation efficiency is low, and the improvement of ion conductivity by solvent plasticization alone is very limited. At the same time, without phosphorus / sulfur flame retardant groups, polyethylene oxide itself is very flammable. When conducting flame retardant tests, it burns violently and drips, and has no self-extinguishing property.
[0035] It can be seen from the data of Comparative Examples 4, 5 and Example 2 that in Comparative Examples 4 and 5, when preparing hyperbranched PEO, the proportion of the main chain A polymer is too high or the proportion of the branched chain B polymer is too high, which has an adverse effect on the ionic conductivity and flame retardant properties of the material. This may be because when the proportion of the main chain A polymer is too high, the cross-linking density of the material is insufficient, the branching structure is loose, and the excessive main chain rigid structure increases the crystallinity, resulting in insufficient flexibility provided by the branch chain, limited segment movement, decreased ionic conductivity of the material, and less influence of conductivity by temperature; when the proportion of the branched chain B polymer is too high, the material is over-cross-linked to form a rigid network, and the segment movement is restricted, thereby causing a sharp drop in ionic conductivity. At the same time, the lack of phosphorus content greatly reduces the flame retardant properties of the material. The sulfur content of the material is too high, but its flame retardant effect is not as significant as that of phosphorus. The excessive sulfur content also destroys the phosphorus-sulfur synergistic flame retardant effect of the material, resulting in a decrease in the overall flame retardant properties.
[0036] It should be understood by those skilled in the art that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A stable flame-retardant gel polymer for electrolyte, characterized in that: The method comprises the following raw materials in parts by weight: 20-30 parts of hyperbranched polyethylene oxide (PEO), 15-20 parts of lithium salt and 60-70 parts of solvent; The specific preparation process of the hyperbranched PEO is as follows: (1) The preparation process of the main chain A polymer is as follows: dissolving trimethylolphosphine oxide in anhydrous toluene, applying a pressure of 3-5 MPa to ethylene oxide to ensure that ethylene oxide is in liquid state, using a continuous flow microchannel reactor to pump liquid ethylene oxide and trimethylolphosphine oxide solution into a mixer through a metering pump, and after uniform mixing, maintaining the temperature at 70-90°C, the pressure at 1-3 MPa, the flow rate at 3-5 ml / min, and the residence time at 5-10 min in the reactor, adding methanol containing 0.1% hydrochloric acid at the discharge port to quench the reaction, and removing the solvent by vacuum distillation. The product is washed with ethanol and dried to obtain the main chain A polymer; (2) The preparation process of the branched B polymer is as follows: 2,2'-[methylenebissulfonyl]diethanol is dissolved in anhydrous tetrahydrofuran, a pressure of 3-5 MPa is applied to ethylene oxide to ensure that ethylene oxide is in liquid state, and liquid ethylene oxide and 2,2'-[methylenebissulfonyl]diethanol solution are pumped into a mixer through a metering pump using a continuous flow microchannel reactor. After uniform mixing, the temperature in the reactor is maintained at 70-80°C, the pressure is 1-3 MPa, the flow rate is 3-5 ml / min, and the residence time is 5-10 min. Methanol containing 0.1% hydrochloric acid is added to the discharge port to quench the reaction, and the solvent is removed by distillation under reduced pressure. The product is washed with ethanol and dried to obtain the branched B polymer; (3) Add methyltrimethoxysilane to an ethanol / water mixed solution, stir at room temperature for 30-60 minutes to obtain a silane solution, add the main chain A polymer and the branched chain B polymer to tetrahydrofuran, stir at room temperature for 30-60 minutes, add the silane solution, heat to 60-80°C, react for 4-8 hours, cool to room temperature, precipitate the product in ether, wash with ethanol, and dry to obtain hyperbranched PEO.
2. The stable flame-retardant gel polymer for electrolyte according to claim 1, characterized in that: In the (1), the weight ratio of trimethylolphosphine oxide, ethylene oxide and toluene is 1:15-25:10-20.
3. The stable flame-retardant gel polymer for electrolyte according to claim 1, characterized in that: In the (2), the weight ratio of 2,2'-[methylenebissulfonyl]diethanol, ethylene oxide and anhydrous tetrahydrofuran is 1:40-50:10-20.
4. The stable flame-retardant gel polymer for electrolyte according to claim 1, characterized in that: The weight ratio of methyltrimethoxysilane, main chain A polymer, side chain B polymer, tetrahydrofuran and ethanol / water mixed solution in (3) is 1:2-4:6-12:100-120:10-20.
5. The stable flame-retardant gel polymer for electrolyte according to claim 1, characterized in that: The ethanol / water mixed solution in (3) refers to a mixture of ethanol and water in a weight ratio of 95:
5.
6. The stable flame-retardant gel polymer for electrolyte according to claim 1, characterized in that: The lithium salt is one or more of lithium perchlorate, lithium trifluoromethanesulfonate, lithium hexafluorophosphate or lithium tetrafluoroborate.
7. The stable flame-retardant gel polymer for electrolyte according to claim 1, characterized in that: The solvent is prepared by mixing triethyl phosphate and ethylene carbonate in a weight ratio of 1:0.
05.
8. The method for preparing the stable flame-retardant gel polymer for electrolyte according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Adding a lithium salt to a solvent and stirring to form a liquid electrolyte; S2. Hyperbranched PEO is added to a liquid electrolyte to obtain a stable flame-retardant gel polymer for electrolyte.
Citation Information
Patent Citations
Method for preparing polyolefin microporous-film supported gel polymer electrolyte film
CN101070398A
Production method for polyolefin membrane support gel rubber polymer electrolyte
CN101220170A
Preparation method and application of reactive type halogen-free flame-retardant polyether glycol
CN105801833A
All-solid-state polyelectrolyte diaphragm and preparation method thereof
CN110707355A
Dual-network physical crosslinking ionic gel electrolyte as well as preparation method and application thereof
CN112542330A